Successful surgical treatment for intrahepatic arterioportal fistula with severe portal hypertension: a case report - Hideyuki Takata; Hiroshi Makino; Tadashi Yokoyama; Hiroshi Maruyama; Atsushi Hirakata; Junji Ueda; Hiroshi Yoshida (Surgical Case Reports, 2019)
Abstract Background Intrahepatic arterioportal fistula (IAPF) is a rare cause of portal hypertension. Interventional radiology (IVR) is generally selected as the first-line therapeutic option. Surgical treatment for IAPF is required in refractory cases of IVR. As the treatment success rate with IVR is high, cases requiring surgical treatment are extremely rare. Case presentation A 54-year-old man was admitted to another hospital complaining of hematemesis due to rupture of the esophageal varices. A computed tomography revealed ascites and arterioportal fistula in the left lobe of the liver. Transcatheter arterial embolization (TAE) was performed to occlude the fistula; however, it could not reach complete occlusion. Thereafter, there were a total of four hematemeses, and six endoscopic variceal ligations were required. The second TAE also failed to reach complete occlusion. He was transferred to our hospital for further treatment. Because liver function was low due to frequent hematemeses and there was also uncontrollable ascites, it was confirmed that hepatectomy could not be performed safely at this time. Therefore, we ligated the left portal branch and ligated and dissected the left gastric vein to decrease portal vein pressure. However, on the 5th day after surgery, the esophageal varices reruptured. As the disappearance of ascites was observed in the postoperative course and the general condition also improved, left hepatectomy was performed to remove IAPF. There was no recurrence of portal hypertension for 1 year and 3 months since hepatectomy. Conclusions This case was difficult to treat with IVR and required surgical treatment. Our experience in the present case suggests that hepatectomy to remove arterioportal fistula was considered effective for improving portal hypertension due to IAPF. However, careful treatment selection according to the patient’s overall condition and clinical course is necessary for IAPF presenting with severe portal hypertension.